Investigation of dielectric relaxation and ion dynamics of Ce0.76Pr0.08Sm0.08Gd0.08O2-δnanocrystalline solid electrolyte ion conductor - Singh M.; Pal V.; Kumar Singh A. (My University, 2025)
The motivation behind this work is to study the dielectric relaxation and ion dynamics of Ce0.76Pr0.08Sm0.08Gd0.08O2-δ oxide ion conductor as solid electrolyte of intermediate temperature solid oxide fuel cells (IT-SOFCs). The sample is single-phase nanocrystalline which crystallizes into cubic fluorite structure as confirmed by Room Temperature X-ray diffraction pattern. The microstructure and elemental composition of sintered pellet have been investigated by scanning electron microscope (SEM) equipped with Elemental dispersive spectroscopy (EDS). The variation of real part of permittivity with frequency showed large values at lower frequency and decreases drastically with increasing frequency. The frequency dependent AC conductivity spectra analysis reveals that the ion dynamics of charge carriers in solid electrolyte material is frequency dependent and obeys the Jonscher's power law. In order to further explore the charge interactions, dielectric tangent loss studies in the frequency range (20 Hz-5 MHz) have been done, which demonstrates that the relaxational peak is associated with the number of mobile charge carriers. © 2019 Elsevier Ltd.